"Put God above All [and He] Will Glorify Your Marriage." Relational Spirituality in Black Couples. Issue 8 (17th November 2021) - Moore, T. J.; Chaney, Cassandra; Skipper, Antonius
Abstract: This study examines the influence of religion on relational spirituality among 33 Black married couples ( N = 66). Previous research has largely relied on samples of White middle-class Americans to assess aspects of relational spirituality within marriages. In contrast, this study uses in-depth qualitative interviews from socioeconomically diverse Black married couples to determine how religion informs perceptions of relational spirituality among an underexamined population. Findings show that Black married couples employ mechanisms of relational spirituality in several ways. Specifically, Black married couples utilize relational spirituality for maintaining and transforming their marriage through: (a) Putting God First; (b) Studying and Applying the Word of God; and (c) Giving Their Life Over to God. Implications of findings from this study suggest that relational spirituality may foster increased marital satisfaction, quality, and commitment, thereby serving as a potential buffer against divorce for Black couples. Implications and recommendations for future research are also discussed.